TEMPLE DESTRUCTION AND THE GREAT MUGHALS’ RELIGIOUS POLICY IN NORTH INDIA: A CASE STUDY OF BANARAS REGION, 1526-1707 - Parvez Alam (Analisa: Journal of Social Science and Religion, 2018)
Banaras also known as Varanasi (at present a district of Uttar Pradesh state, India) was a sarkar (district) under Allahabad Subah (province) during the great Mughals period (1526-1707). The great Mughals have immortal position for their contributions to Indian economic, society and culture, most important in the development of Ganga-Jamuni Tehzeeb (Hindustani culture). With the establishment of their state in Northern India, Mughal emperors had effected changes by their policies. One of them was their religious policy which is a very controversial topic though is very important to the history of medieval India. There are debates among the historians about it. According to one group, Mughals’ religious policy was very intolerance towards non-Muslims and their holy places, while the opposite group does not agree with it, and say that Mughlas adopted a liberal religious policy which was in favour of non-Muslims and their deities. In the context of Banaras we see the second view. As far as the destruction of temples is concerned was not the result of Mughals’ bigotry, but due to the contemporary political and social circumstances. Mostly temples were destroyed during the war time and under political reasons. This study is based on primary Persian sources and travelogues, perusal study of Faramin (decrees), and modern works done on the theme. Besides this, I have tried to derive accurate historical information from folklore, and have adopted an analytical approach. This article showed that Mughals’ religious policy was in favour of Pundits (priests), Hindu scholars and temples of Banaras; many ghats and temples were built in Banaras with the full support of Mughals. Aurangzeb made many grants both cashes and lands to priests and scholars of Banaras.